2020
DOI: 10.1177/0956462420943704
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, retention, and outcomes in a demonstration project of pre-exposure prophylaxis among female sex workers in public health centers in Senegal

Abstract: The Senegal pre-exposure prophylaxis (PrEP) Demonstration Project was an open-label cohort study assessing the delivery of daily oral PrEP to HIV-negative female sex workers (FSWs) in four Ministry of Health (MoH)-run clinics in Dakar, Senegal. We assessed uptake, retention in care, and adherence over up to 12 months of follow-up as well as HIV infection rates. Between July and November 2015, 350 individuals were approached and 324 (92.6%) were preliminarily eligible. Uptake was high, with 82.4% of eligible pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
5
30
4
Order By: Relevance
“…Smaller studies (TDF2-Botswana 9 and Bangkok-TDF 29 ) with better adherence (>75%) did show substantial effectiveness (RR 0.35, 95%CI 0.22-0.54), 21 and a recent demonstration trial 15) 0 (0) 0 0 14 (19) Not interested 0 (0) 1 ( 12) 4 ( 14) 6 ( 22) 0 (0) 0 0 11 (15) Other illness 0 (0) 0 (0) 2 ( 7) 1 ( 4) 1 (33) 0 0 4 (5) Daily PrEP inconvenient 1 ( 14) 1 ( 12) 2 ( 7) 0 (0) 0 (0) 0 0 4 (5) Partner not Supportive 0 (0) 1 ( 12) 1 ( 3) 2 ( 7) 0 (0) 0 0 4 (5) In police custody 0 (0) 0 (0) 0 (0) 1 ( 4) 1 (33) 0 0 2 (3) Embarrassed 0 (0) 0 (0) 2 ( 7) 0 (0) 0 (0 2) 32 ( 5) 43 ( 7) 25 ( 4) 23 ( 4) 39 ( 7) Took 1 pill every day last month, n (%) 320 ( 59) 289 ( 45) 269 ( 43) 249 ( 42) 145 ( 24) N/A Missed ≥ 7 days since last visit, n (%) 63 ( 12) 116 ( 18) 123 ( 20) 118 ( 20) 119 ( 20) 129 ( 22) Longest stretch (days) of nonadherence, median (Q1-Q3) from Senegal demonstrated high levels of retention and no incident HIV infections. 30 In our trial, most tested women had TDF levels suggestive of consistent TDF-FTC use, particularly among those tested in later visits. Importantly, there were no HIV seroconversions detected.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Smaller studies (TDF2-Botswana 9 and Bangkok-TDF 29 ) with better adherence (>75%) did show substantial effectiveness (RR 0.35, 95%CI 0.22-0.54), 21 and a recent demonstration trial 15) 0 (0) 0 0 14 (19) Not interested 0 (0) 1 ( 12) 4 ( 14) 6 ( 22) 0 (0) 0 0 11 (15) Other illness 0 (0) 0 (0) 2 ( 7) 1 ( 4) 1 (33) 0 0 4 (5) Daily PrEP inconvenient 1 ( 14) 1 ( 12) 2 ( 7) 0 (0) 0 (0) 0 0 4 (5) Partner not Supportive 0 (0) 1 ( 12) 1 ( 3) 2 ( 7) 0 (0) 0 0 4 (5) In police custody 0 (0) 0 (0) 0 (0) 1 ( 4) 1 (33) 0 0 2 (3) Embarrassed 0 (0) 0 (0) 2 ( 7) 0 (0) 0 (0 2) 32 ( 5) 43 ( 7) 25 ( 4) 23 ( 4) 39 ( 7) Took 1 pill every day last month, n (%) 320 ( 59) 289 ( 45) 269 ( 43) 249 ( 42) 145 ( 24) N/A Missed ≥ 7 days since last visit, n (%) 63 ( 12) 116 ( 18) 123 ( 20) 118 ( 20) 119 ( 20) 129 ( 22) Longest stretch (days) of nonadherence, median (Q1-Q3) from Senegal demonstrated high levels of retention and no incident HIV infections. 30 In our trial, most tested women had TDF levels suggestive of consistent TDF-FTC use, particularly among those tested in later visits. Importantly, there were no HIV seroconversions detected.…”
Section: Discussionmentioning
confidence: 52%
“…Smaller studies (TDF2-Botswana 9 and Bangkok-TDF 29 ) with better adherence (>75%) did show substantial effectiveness (RR 0.35, 95%CI 0.22–0.54), 21 and a recent demonstration trial from Senegal demonstrated high levels of retention and no incident HIV infections. 30 In our trial, most tested women had TDF levels suggestive of consistent TDF-FTC use, particularly among those tested in later visits. Importantly, there were no HIV seroconversions detected.…”
Section: Discussionmentioning
confidence: 52%
“… 12 In Senegal, adherence measured by MEMS (was initially 80% but dropped rapidly to 50% in the first 2 months). 13 Moreover, both these studies did not evaluate factors associated with adherence.…”
mentioning
confidence: 99%
“…The daily uptake of PrEP is not always adapted to FSWs’ life context. More broadly, the mobility of FSWs and the stigmatization they face from their neighborhood or healthcare professionals complicate their access to care and their retention in demonstration projects [ 20 , 21 , 46 , 47 ]. Beyond the development of community support and mobile clinics to limit these difficulties, exploring the suitability of long-acting PrEP to this population could be useful [ 48 ].…”
Section: Discussionmentioning
confidence: 99%